2020
DOI: 10.1080/07391102.2020.1779132
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bioactive compounds fromGlycyrrhiza glabraas possible inhibitor of SARS-CoV-2 spike glycoprotein and non-structural protein-15: a pharmacoinformatics study

Abstract: Aim: In view of the strong immunomodulatory and antiviral activity of andrographolide and its derivative, the present study aimed to investigate the binding a nities of andrographolide and its derivative 14deoxy-11,12-didehydroandrographolide with 3 major targets of COVID-19 i.e. 3CLpro, PLpro and spike protein followed by their gene-set enrichment analysis with special reference to immune modulation. Materials and methods: SMILES of the compounds were retrieved from DigepPred database and the proteins identi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 58 publications
3
98
0
9
Order By: Relevance
“…From binding energy and interaction studies, Saikosaponins U and V displayed the strongest affinity towards the S protein ( Sinha et al, 2020a ). Similarly, a molecular docking simulation study of 20 compounds and an additional simulation study using molecular dynamics (MD) found that components of glycyrrhizic acid and glyasperin A displayed high binding affinity towards the S protein ( Sinha et al, 2020b ). COVID-19 principally spreads through the respiratory tract, and so the pharynx is a location that the virus can be found in high concentration.…”
Section: Discussionmentioning
confidence: 99%
“…From binding energy and interaction studies, Saikosaponins U and V displayed the strongest affinity towards the S protein ( Sinha et al, 2020a ). Similarly, a molecular docking simulation study of 20 compounds and an additional simulation study using molecular dynamics (MD) found that components of glycyrrhizic acid and glyasperin A displayed high binding affinity towards the S protein ( Sinha et al, 2020b ). COVID-19 principally spreads through the respiratory tract, and so the pharynx is a location that the virus can be found in high concentration.…”
Section: Discussionmentioning
confidence: 99%
“…ORF1a/b located at the 5′ end encodes 16 non-structural proteins (NSPs) called NSP1 to NSP16. In addition, other ORFs at the 3′ end encode accessory and structural proteins [ [16] , [17] , [18] ], including spike (S) protein responsible for anchoring the virus to the receptor and subsequent fusion of the membrane, thereby mediating the entry of the virus into the cell; the envelope protein (E) plays a pivotal role in the assembly and release of the virus in addition to exercising the ion channel function necessary for the pathogenesis of SARS-CoV-2. The membrane protein (M) assists in maintenance of the membrane curvature and binding to the nucleocapsid whereas the nucleocapsid protein (N) is involved in the packaging of the viral genome encapsulated in the viral particles and its interaction with the M and NSP3 proteins [ 19 ].…”
Section: Sars-c0v-2mentioning
confidence: 99%
“…Glycyrrhizin was found more active than ribavirin, 6-aziridine, pyrazofurin and the Mycophenolic acid (Cinatl et al, 2003). Another study aimed at identifying in-silico the activity of molecules derived from licorice against two targets of SARS-CoV-2, the Spike protein and the endoribonuclease Nsp 15, has shown, via the analysis of molecular docking and molecular dynamics, that Glycyrrhizic Acid has a high af inity which can inhibit the Spike protein of SARS-CoV-2 (Sinha et al, 2020).…”
Section: Saponosidesmentioning
confidence: 99%